2011
DOI: 10.5468/kjog.2011.54.9.561
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell adenocarcinoma arising from adenomyosis mimicking leiomyoma: A case report

Abstract: The incidence of cancer from adenomyosis is rare. Previously, only two cases of clear cell adenocarcinoma (CCA) arising from adenomyosis have been reported in English literature. Here, we report a case of CCA arising from adenomyosis. A 52-year-old postmenopausal Korean woman presented with complaints of vaginal bleeding and back pain. Endometrial biopsy revealed endometrial polyp with atrophic change and transvaginal ultrasonography showed myomas with cystic change. Magnetic resonance imaging revealed a cysti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 8 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…12 Kumar and Anderson pointed out the necessity of a transition between the benign adenomyotic endometrial and carcinomatous glands to prove a diagnosis of ectopic endometriumderived adenocarcinoma. 11 In our case, although there were foci of isolated clear cell adenocarcinoma in the endometrium, the diagnosis was compatible with clear cell adenocarcinoma arising from adenomyosis because the tumor was mainly located in the adenomyotic cyst wall in the myometrium as in situ carcinoma with an obvious transition from nonneoplastic epithelium along with endometrial stromal cells. Furthermore, immunohistochemical analysis demonstrated that some of the epithelial cells of the adenomyotic cyst were ER À and p53 + , the same staining pattern as that of clear cell adenocarcinoma, suggesting that the epithelial cells of the adenomyotic cyst, which histologically appeared somewhat atypical but non-neoplastic, harbored early genetic abnormalities for carcinogenesis and precancerous cells, from which clear cell adenocarcinoma arose.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…12 Kumar and Anderson pointed out the necessity of a transition between the benign adenomyotic endometrial and carcinomatous glands to prove a diagnosis of ectopic endometriumderived adenocarcinoma. 11 In our case, although there were foci of isolated clear cell adenocarcinoma in the endometrium, the diagnosis was compatible with clear cell adenocarcinoma arising from adenomyosis because the tumor was mainly located in the adenomyotic cyst wall in the myometrium as in situ carcinoma with an obvious transition from nonneoplastic epithelium along with endometrial stromal cells. Furthermore, immunohistochemical analysis demonstrated that some of the epithelial cells of the adenomyotic cyst were ER À and p53 + , the same staining pattern as that of clear cell adenocarcinoma, suggesting that the epithelial cells of the adenomyotic cyst, which histologically appeared somewhat atypical but non-neoplastic, harbored early genetic abnormalities for carcinogenesis and precancerous cells, from which clear cell adenocarcinoma arose.…”
Section: Discussionsupporting
confidence: 60%
“…A PubMed search performed using the key words 'uterine clear cell adenocarcinoma' and 'adenomyosis' revealed five cases published between 1994 and 2011. [7][8][9][10][11] Herein, we report the sixth case of clear cell adenocarcinoma arising from adenomyosis (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the "unbiased study endpoints" domain, the risk of bias was low in 14 studies [13,14,17,18,20,24,[29][30][31][32][33]37,39,40,42], unclear in 11 studies [15,16,19,22,23,[26][27][28]34,35], and high in six studies [12,21,25,36,38,41]; in particular, in the studies at high risk of bias, Colman and Rosenthal's criteria were only partially fulfilled.…”
Section: Assessment Of Risk Of Bias Among Studiesmentioning
confidence: 98%
“…For the "patient selection" domain (when applicable), two studies were considered at low risk of bias [12,42], while two studies were judged as having unclear risk of bias [34,35]. For the "study endpoints" domain, the risk of bias was considered low in 15 studies [12][13][14]17,18,20,21,24,[29][30][31][32][33]37,41,42], while it was unclear in 16 studies [15,16,19,22,23,[25][26][27][28][34][35][36][38][39][40].…”
Section: Assessment Of Risk Of Bias Among Studiesmentioning
confidence: 99%